Fine mapping a quantitative trait locus underlying seedling resistance to gummy stem blight using a residual heterozygous lines-derived strategy in cucumber - Han, Jianan; Dong, Shaoyun; Liu, Xiaoping; Shi, Yanxia; Beckles, Diane M.; Gu, Xingfang; Miao, Han; Zhang, Shengping (Frontiers in Plant Science, 2022)
Gummy stem blight (GSB), caused by Didymella bryoniae, is one of the most devastating diseases that severely reduces cucumber production. One of the most effective strategies to control GSB would be to develop resistant varieties. Although several GSB-resistant QTLs have been reported, causal genes for GSB resistance have not yet been identified in cucumber. A novel loci gsb3.1 for seedling GSB resistance from the ‘PI 183967’ genotype was previously identified in a 1.7-Mb interval on chromosome 3. In this study, we developed a residual heterozygous line-derived strategy from Recombinant Inbred Lines to perform fine mapping, and with this approach, the gsb3.1 locus was narrowed down to a 38 kb interval. There were six predicted genes at the gsb3.1 locus, four of which differed in expression in the GSB-resistant compared to the susceptible lines after fungal inoculation. These candidate genes (Csa3G020050, Csa3G020060, Csa3G020090, and Csa3G020590) within the gsb3.1 locus could be helpful for the genetic study of GSB resistance and marker-assisted selection in cucumber. Phylogenetic analyses indicated that the resistant gsb3.1 allele may uniquely exist in the wild species present in the Indian group, and that nucleotide diversity was significantly reduced in cultivated accessions. Therefore, gsb3.1 allele could be introgressed into existing commercial cultivars and combined with other resistance QTLs to provide broad-spectrum and robust GSB-resistance in cucumber.